Professional Ideals of Secondary School's Pupils - Stulpinas, Tomas (Acta Paedagogica Vilnensia, 2003)
1378 pupils of the fourth classes and 636 pupils of the eighth-tenth classes have participated in the questionnaire. The fields of the services, art activities, law and pedagogics have rated highest. The professions of a scientist, manager, worker were unpopular. The basic differences in priorities regarding age and sex of the respondents have been established. The girls prefer specialities of higher education. The initial stage of motivation process – the attachment is dominating. The younger respondents underline more the wish to help people, the elder ones – achievements in personal welfare. 7,9% of teenagers still have not decided about their future working activities. The systematic work on professional orientation of pupils is necessary.
Keywords: professional orientation; professional ideals; school; school's pupils